The obligatory research on the pupils’ sense of self-security in youth educational centers and youth socio-therapy centers – from the current law perspective - Justyna Siemionow (Probacja, 2022)
Youth social rehabilitation and socio-therapy centres are places for socially maladjusted adolescents aged between 12 and 19 who have special educational needs, require special interactions and therapy as well as suffer from behavioural and emotional disorders. The role of these institutions is to prepare young people for independent, creative and responsible life in non-institutional environment. The study of sense of self-security is one of the main obligatory tasks which should be performed minimum twice a year in each institution as regulated by the Polish law according to the Polish Ministry of Education and Science which administers all the centres. This study aims at recognizing how youth social rehabilitation centres and socio-therapy centres conduct the surveys connected with the sense of adolescents’ self-security when they are in residential care. The article presents the quantitative research with over ninety participants, which constitutes almost 60% of all these institutions in Poland. The participants responded to the online questionnaire. The main research problem is the way the process of examining youths' sense of security in these institutions is carried out and the factors it depends on. The results show that there are no differences between these two kinds of researched institutions in investigating the youths’ sense of self-security. Youth social rehabilitation and socio-therapy centres fully perform this duty but do so differently. The results of the research in the article also show that it is necessary to analyze further the information and data about youth’s self-security.